Studies on Industrial Effluents Quality with Reference to Heavy Metals Content - SOLANKI, R.B.; SAWANT, C.P. (Asian Journal of Chemistry, 2010)
This paper reports the heavy metal content in some industrial effluents from Gujarat Industrial Development Center (GIDC) area of Ankleshwar. The effluent in the area is discharged into sewer and finally goes to river and then goes to Arabian Sea. The metals like Fe, Cr, Cd, Ni, Cu, Mn, Zn, As, Al and Hg, B, Be, Sb, Mo were determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The results are compared with WHO and Indian standards.